The Influence of Beauty Vloggers on Gen Z Consumers' Purchase Intentions towards Local Brand Cosmetics Mediated by Brand Image - Golan Hasan; Tasya Gebee Hasvia (International Journal of Economics Development Research (IJEDR), 2023)
This study examines the determinants that can influence the purchase intention of Gen Z consumers towards local brand cosmetic products mediated by brand image. This research can be categorized as Causal Comparative research, which aims to show the relationship between independent and dependent variables. The population in this study is targeting people who know local brand cosmetics in Batam City. The sample that is the focus of this research is people aged 18-26 years (Gen Z) who have seen beauty vloggers review local brand cosmetics, know local cosmetic brands Wardah, Emina, Make Over, Something, Dear Me Beauty and Luxcrime and are interested to use local brand cosmetics. The data collected in this study were obtained from 420 respondents by distributing questionnaires via the Google form. The data analysis technique used in this study is linear regression using SmartPLS software. The results of the study show that Beauty Vlogger has no significant effect on Purchase Intention. Meanwhile e-WOM, Attitude, Subjective Norm, Perceived Behavioral Control, and Brand Image have a positive and significant effect on Purchase Intention. Then there is also a significant relationship between beauty vlogger and purchase intention which is mediated by brand image.